The Effect of Contextual Teaching Learning Model on Number Material on the Motivation of Elementary School Students in Grade 1 SD N 70 Palembang - Safira, Alda; Arni, Yusni; Nadila, Putri; Pratiwi, Selly Ayu; Batistuta, Batistuta (CV. PUSDIKRA MITRA JAYA, 2025)
This study sought to ascertain how the contextual learning paradigm affected the learning results of first-graders studying addition and subtraction in mathematics classes at SD Negeri 70 Palembang. This kind of study uses a nonequivalent control group design and is a quasi-experiment. Fifty first-graders served as the research subjects. A multiple-choice exam with ten items was the tool utilized. For Window 2.6.44, data analysis was conducted using an independent T test with assistance from Jamovi. The findings demonstrated that students who received instruction using contextual learning models had a higher comprehension of mathematical concepts than students who received instruction using traditional learning models.